A Cobalt‐Free Li(Li0.17Ni0.17Fe0.17Mn0.49)O2 Cathode with More Oxygen‐Involving Charge Compensation for Lithium‐Ion Batteries. Issue 11 (30th April 2019) - Wei, Hezhuan; Cheng, Xiaolu; Fan, Hongwei; Shan, Qian; An, Shengli; Qiu, Xinping; Jia, Guixiao
Abstract: High‐energy‐density and low‐cost lithium‐ion batteries are sought to meet increasing demand for portable electronics. In this study, a cobalt‐free Li(Li0.17 Ni0.17 Fe0.17 Mn0.49 )O2 (LNFMO) cathode material is chosen, owing to the reversible anionic redox couple O 2− /O − . The aim is to elucidate the Fe‐substitution function and oxygen redox mechanism of experimentally synthesized Li(Li0.16 Ni0.19 Fe0.18 Mn0.46 )O2 by DFT. The redox processes of cobalt‐containing Li(Li0.17 Ni0.17 Co0.17 Mn0.49 )O2 (LNCMO) are compared with those of LNFMO. Redox couples including Ni 2+ /Ni 3+ /Ni 4+, Fe 3+ /Fe 4+ or Co 3+ /Co 4+, and O 2− /O − are found, confirmed by a X‐ray photoelectron spectroscopy, and explained by redox competition between O and transition metals. In LNFMO and LNCMO, O ions with an Li‐O‐Li configuration readily participate in oxidation, and the most active O ions are coordinated to Mn 4+ and Li + . Oxidation of O in LNCMO is triggered earlier, along with that of Co. Fe substitution activates O ions, contributes additional oxygen redox charge compensation of 0.44 e per formula unit, avoids concentrated accumulation of oxygen oxidation, and improves structural stability. This work provides new scope for designing cobalt‐free, low‐cost, and higher‐energy‐density cathode materials for Li‐ion batteries. Abstract : Triggering the neighbors : Co‐free, Fe‐containing, Li‐rich oxide Li(Li0.17 Ni0.17 Fe0.17 Mn0.49 )O2 is studied as a cathode material for Li‐ion batteries by DFT. Fe triggers neighboring O ions through Jahn–Teller distortion to participate in oxidation, and thus avoids concentrated accumulation of oxygen oxidation and improves the structural stability. This provides new scope for designing cobalt‐free, low‐cost, and higher‐energy‐density cathode materials for Li‐ion batteries.